Optimalisasi Penggunaan Media Sosial dalam Mengkampanyekan Keberadaan Rumah Singgah Kanker Kepada Masyarakat di Komunitas Mufeedah - Dewi, Eriyanti Nurmala (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
CANCER Shelter House is a place to live for cancer survivors from underprivileged circles when carrying out outpatient care in the city of Bandung. The existence of this Cancer Shelter is not widely known to the public. The Mufeedah Community is a community that cares about the existence of the Cancer Shelter. However, there are still difficulties in socializing the existence of the Cancer Shelter to the public. Social media, especially Facebook (FB) and WahtsApp (WA) are the most widely used social media in Indonesia. This community service (AbdiMas) aims to help the Mufeedah Community in disseminating the campaign for the existence of the Cancer Shelter to the public by helping design FB, WA content in the form of posters, narratives, and short videos. In addition, assisting the management of FB and WA Stories with content that has been designed. The results are very significant. The public is more familiar with the Cancer Shelter from the comments given by netizens in the FB comment column and WA Story status. The number of donors has also increased so that the Mufeedah Community can provide basic food assistance and healthy food as well as facilities and infrastructure for the Cancer Shelter and the existence of the Cancer Shelter.